Achieving research excellence Zimbabwean universities: a review based on the eight anchor elements characterising excellent companies - Duve, Richard (Midlands State University, 2014)
This paper discusses the importance of achieving quality university research and how the research contributes to the success of industry and commerce in Zimbabwe. The research boards in universities are under stress due to limited resources and budgetary constraints. There are eight anchor elements that characterize most successful companies in United States of America that can be used as a framework of achieving research breakthrough in institutions of higher learning in Zimbabwe. Being stakeholder driven institutions of, the issue underpins the importance of being more closer to the customers in so far as research excellence can be achieved. The author further seeks to add a ninth anchor element, leadership which is the umbilical cord which houses the 8 anchor elements that characterise companies that have achieved breakthrough in business strategies. Lastly, the author assesses the importance of magnetic leadership for achieving research breakthrough in universities.